A self-healing data management architecture for IoT applications: a case study of smart urban farming on high-rise buildings - Hamzah, Hairul Aini; Hamzah, Raseeda; Jamil, Nursuriati; Abdul Rahim, Siti Khatijah Nor; M. Asmuei, Abdul Rahmad; Mushaimi, Muhd Aizzad; Noor, M.H.M; Abu Samah, Khyrina Airin Fariza (World Academy of Research in Science and Engineering, 2020)
This paper presents the containerization of virtualization method that is done to execute distributed application for smart urban farming system. Containerization is a virtualization method for executing distributed applications without the need of virtual machines. However, when dealing with container downtime, a backup solution is needed to ensure that no data lost and to ensure container is in functioning. A container downtime might be caused by connectivity failure or maximum CPU capacity utilization. Therefore, a micro services-based system was developed by leveraging on containerization technology such as Docker for its lightweight footprint in terms of infrastructure resources and container orchestration capabilities from Kubernetes to enable scalability and reliability of the overall system. The results showed that efficient data monitoring and management with the added advantage of self-healing nature of Kubernetes platform was achieved.